Pengenalan Nilai Pendidikan Khitan Laki-Laki Dalam Syariat - Adam Jakrinur; Fathur Rahman; M. Iqbal Ramadhan; Mhd Taura Zilhazem; Yogi Permana; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Islam is a religion that is very concerned about cleanliness and health. Many problems that have an impact on the cleanliness and health of the body cannot be ignored in this religion. One of them is about circumcision which has been medically recognized to have great benefits. Children as the mandate of Allah SWT. In circumcision, it turns out that it contains educational values that can be taken in order to lead the child to become a pious Muslim person. So, circumcision is something parents must do in an effort to educate their children.